AN ANALYSIS OF THE FACTORS CONTRIBUTING TO THE FAILURE OF RIDE-HAILING ADOPTION IN DEVELOPING REGIONS THROUGH THE LENS OF THE DIFFUSION OF INNOVATION MODEL: A CASE STUDY OF OKE-JEK IN MANOKWARI REGENCY - Roberth Yembise; Dedi Iskandar Inan; Ratna Juita; Muhamad Indra (Jurnal Sistem Informasi, 2025)
This study analyzes the use of the Oke-Jek platform as a ride-hailing service in developing regions. The objective of the study is to identify the factors that hinder the adoption of Oke-Jek as a ride-hailing service in such areas. Currently, the utilization of Oke-Jek remains limited, particularly in regions like West Papua, leading to a research gap regarding the adoption of this service in the area. This study employs the Diffusion of Innovation Theory as its conceptual framework. Data were collected through a Google Forms-based questionnaire, with a total of 112 respondents. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The main findings indicate that the proposed model demonstrates good reliability and validity, with an R² value of 0.628, meaning that Behavioral Intention to Use explains 62% of the variance in the use of Oke-Jek. Furthermore, the results confirm that Compatibility, Relative Advantage, and Complexity are significant factors influencing the adoption of Oke-Jek among respondents. The implications of this research support the development of ride-hailing services in developing regions. These findings can be used to design effective strategies for increasing the adoption of Oke-Jek in West Papua. In addition to providing theoretical insights, this study also offers strategies for the evaluation and optimization of ride-hailing services.   Keywords: Developing Regions, Diffusion of Innovation, Partial Least Squares Structural Equation Modeling, Ride-hailing, Technology adoption